(untitled) (Research, Society and Development, 2022)
This work aimed to present a study on the importance of implementing the Military Penal Execution Regulation of the Military Police of the State of Tocantins - PMTO. The research was based on the qualitative approach in theoretical and documentary references, as well as access to quantitative data of prisoners held in the Military Police Units - UPM of the PMTO in the year 2019. The bibliographic and documentary research demanded the methodology of scientific work, with focus on the analysis of general aspects and concepts of Military Penal Execution. In addition, there were different doctrinal understandings regarding the application of the Penal Execution Law - LEP in Military Justice. Based on the above, data and information were listed, institutional deficiencies were analyzed and discussed, and the implementation of the Military Penal Execution Regulation was proposed as a legal mechanism to control the discipline of military and common prisoners who are in custody under the of PMTO Prison Units.